Production of thermostable and organic solvent tolerant lipase isolated bacteria using palm kernel cake (PKC) - Nurul Hidayah binti Mohd Zubairi (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
Palm Kernel Cake (PKC) as a by-product of oil palm industry contained a lot of nutrients that may contribute benefit to the industry and directed studies towards utilization of this substrate in order to produce enzymes like lipases. There are many reports on the production of microbial lipases with single property of thermostable or organic solvent tolerant which limit the complete reactions in synthesis of biochemicals. Very few lipases have been reported having both characteristics such as thermostable and organic solvent-tolerant suitable in fermentation of solid wastes for industrial processes. This research focused on the selection of potential bacterial strains that having ability to grow effectively in palm kernel cake (PKC) and produce high amount of thermostable and solvent tolerant (TS-OST) lipase. The work involved the isolation of thermophilic and organic solvent tolerant bacterial strains, optimization of fermentation conditions using PKC as a basal medium as well as characterization of produced lipase in terms of stability. A total of 11 bacterial strains have successfully isolated with capability of producing lipase. After both qualitatively and quantitatively screening of lipase, strain PKC-P1 showed highest lipase activity (11.13U/g). A novel thermophilic and organic solvent tolerant bacteria Bacillus smithii strain PKC-P1 was successfully isolated from PKC and has been identified excreted TS-OST lipase. Optimization process was observed that combination of Plackett Burman Design (PBD), One-factor-at-a-time (OFAT) and Faced Centered Central Composite Design (FCCCD) experimental model were resulted to increment of lipase activity from PBD (42.8 U/g) to OFAT (46.6 U/g) and about 58.92 U/g at FCCCD process. A successful improvement of lipase production was achieved at the end of this study. Besides that, kinetic studies revealed that specific growth rate (µ) and doubling time (td) were obtained with the value of 0.0216 h-1 and 32.10 hours, respectively. Maximum specific growth rate (µmax) as well as Monod constant (Ks) were estimated by Lineweaver-Burk plot and the values obtained were 0.378h-1 and 23.82 g/L respectively. In addition, yield coefficient also was studied, and the results obtained for Yp/x, Yp/s and Yx/s were 0.662gg-1, 3.57gg-1 and 0.152gg-1, respectively. This research was completed by characterization of lipase produced. The results showed that lipase had good stability at pH 7.0 and 8.0 as well as at temperature of 65oC. Lipase also was observed to have good stability at low concentration of polar and non-polar organic solvents (except ethanol) as well as at low concentration of non-ionic surfactants (Triton X-100 and Tween-80). In addition, its capability to adapt with thermophilic condition as well as its good stability with the presence of several organic solvents gave high opportunity for this enzyme to be applied in industry.